2003
DOI: 10.1007/s11743-003-0245-6
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of phospholipid vesicular structures into mixed micelles of zwitterionic surfactants

Abstract: Interactions between the binary combination of dimethyltetradecylammoniopropanesulfonate (TPS) and L-α-phosphatidylcholine (PC), 1,2-didecanoyl-sn-glycero-3-phosphocholine, and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine in the aqueous bulk phase were evaluated with the help of pyrene fluorescence (I 1 /I 3 ) measurements by studying the aggregation processes of TPS in pure water and in the presence of 7-36 µM of fixed concentrations of each lipid. The fluorescence measurements showed that TPS monomers undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Surfactants play a key role in nanomedicine as building blocks of functional aggregates, as nanoparticle stabilisers and drug delivery systems, besides their great variety of properties (e.g., solubilisation, detergency, wetting and foaming ability) [ 18 , 19 , 20 ]. These aspects are strongly related to their molecular structure and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants play a key role in nanomedicine as building blocks of functional aggregates, as nanoparticle stabilisers and drug delivery systems, besides their great variety of properties (e.g., solubilisation, detergency, wetting and foaming ability) [ 18 , 19 , 20 ]. These aspects are strongly related to their molecular structure and composition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lysolipid detergents can increase fluidity and decrease the bending rigidity of phospholipid membranes, exhibiting a positive correlation between chain length and bending rigidity. , Furthermore, the same investigation found that the partitioning coefficients of the same lysolipid detergents within membranes correspond with acyl chain length . This is similarly true for amphiphiles with sulfobetaine headgroups doped into lipidic bilayers, longer hydrophobic chain tails correlate with stronger partitioning and a higher potential to micellize. , Further investigation found that hydrophobic chain tails of DDAPS can fold back on themselves within micellar structures, foregrounding their potential for packing mismatch . Such results align with our proposal above, signifying that molecule-specific hydrophobic chain tail mismatch likely determines the value of D hh and its relative regressions.…”
Section: Resultsmentioning
confidence: 99%
“…Surfactants have dynamic surface-active properties that enable them to lower the surface tension of water [24]. The surfactant monomers get adsorbed at the interface, and above a specific threshold concentration called the critical micelle concentration (CMC), the excess surfactant monomers self-associate to form micellar aggregates [25,26] In general, a minimum of 20 seconds of hand washing with soap and water is shown to be effective in the removal of oily particles [51,52]. However, complete inactivation of viruses within such a short time of interaction cannot be asserted by the membrane rupture mechanism.…”
Section: Chemistry and Cleansing Action Of Soapmentioning
confidence: 99%